Emulador de Turbina de Geração Eólica com GSIP Empregando Inversor de Frequência - Carminati, Rachel Campagnaro (2017)
In this work the assembly of a static bench for emulation of wind power generation systems using permanent magnet synchronous generator is proposed. Unlike the existing dynamical benches, which use a motor coupled to a generator, the system uses a frequency inverter properly controlled by a digital module to represent the turbine-generator behavior. In this study, topics related to the conceptual and operational elements that describe the expected behavior of a wind turbine are discussed, in order to allow a near-real emulation to occur. The main characteristics of the equipment that have been configured to behave in imitation of the wind turbine and the synchronous generator are also discussed. The bench was set up in the LEPAC laboratory of the Federal University of Espírito Santo, with the premise of practicality and low cost, and for this made use of equipment already existing in the institution. The control module was shipped on an Arduino board, communicating with a PC. The WEG CFW09 inverter was used. Several wind profiles and some load conditions were tested. The results obtained, shown and analyzed, prove the validity of the proposed methodology.